STUDENTS’ DISCERNMENT OF BUILDING MAINTENANCE PRACTICES IN BELL UNIVERSITY OF TECHNOLOGY, OTA, OGUN STATE - A.O., Ogungbemi; Omunagbe, I.A.; Salisu, H.A.; Olaitan, P.A.; King, O.R.; Akingbade, O.H. (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
This study examined the students’ discernment of building maintenance practices in the study area, to achieved this, two hundred and fifty respondents comprising majorly students’ and staff of maintenance section were conventionally administered within the study area using descriptive statistics. The result of the findings found that majorly emergency inspection of building maintenance, direct labour was major practices, lack of regular planned inspection strategies culture and maintenance of building services in the campus scarcely necessitates before the commencement of every new session. Although they had maintenance section, but do not get more support and carry along in every maintenance operation.